Analysis of Influencing Factors of Serum Stress Index and Prognosis of HICH Patients by Different Anesthesia Methods Combined with Small Bone Window Microsurgery. (25th March 2022) - Zhao, Guangping; Shi, Jiong; Chen, Yongxue
Abstract : In order to investigate the effects of sevoflurane on the serum stress index level and prognosis of patients with hypertensive cerebral hemorrhage (HICH) during small bone window microsurgery, a total of 102 HICH patients are selected for analysis. MAP values in both groups decreased significantly at T1 and T2 (P < 0.05 ), and the changes in MAP and HR indexes in the sevoflurane combined group were more stable than those in the control group. The time of postoperative awakening in the sevoflurane combined group decreases significantly than the control group (P < 0.001 ). The levels of T-AOC and GSH-Px in both groups increase significantly after operation, and those in the sevoflurane combined group increase significantly than the control group (P < 0.001 ). The levels of MDA and 8-OHDG in the sevoflurane combined group decrease significantly than the control group after operation (P < 0.05 ). Spearman correlation coefficient analysis shows that the levels of T-AOC and GSH-Px are negatively correlated with the prognosis of HICH patients, while MDA and 8-OHDG are positively correlated with the prognosis of HICH patients (P < 0.001 ). Sevoflurane interventional anesthesia has a high anesthetic effect in small bone window microsurgery, which has positive effects on controlling blood pressure of HICH patients, shortening postoperative recovery time and improving patients' stress response and neurological function. This paper conducts an in-depth analysis of the prognosis of HICH patients, indicating that the prognosis of HICH patients is closely related to their serum stress indicators T-AOC, GSH-Px, MDA, and 8-OHDG, providing a new direction for follow-up clinical diagnosis and treatment of HICH patients and accurate prognosis assessment.